Preparation of nanocellulose from Imperata brasiliensis grass using Taguchi method - Benini, Kelly Cristina Coelho de Carvalho [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Rezende, Mirabel Cerqueira; Arantes, Valdeir (Elsevier, 2018)
Cellulose nanoparticles (CNs) were prepared by acid hydrolysis of the cellulose pulp extracted from the Brazilian satintail (Imperata Brasiliensis) plant using a conventional and a total chlorine free method. Initially, a statistical design of experiment was carried out using Taguchi orthogonal array to study the hydrolysis parameters, and the main properties (crystallinity, thermal stability, morphology, and sizes) of the nanocellulose. X-ray diffraction (XRD), fourier-transform infrared spectroscopy (FTIR), field-emission scanning electron microscopy (FE-SEM), dynamic light scattering (DLS), zeta potential and thermogravimetric analysis (TGA) were carried out to characterize the physical-chemical properties of the CNs obtained. Cellulose nanoparticles with diameter ranging from 10 to 60 nm and length between 150 and 250 nm were successfully obtained at sulfuric acid concentration of 64% (m/m), temperature 35 °C, reaction time 75 min, and a 1:20 (g/mL) pulp-to-solution ratio. Under this condition, the Imperata Brasiliensis CNs showed good stability in suspension, crystallinity index of 65%, and a cellulose degradation temperature of about 117 °C. Considering that these properties are similar to those of nanocelluloses from other lignocellulosics feedstocks, Imperata grass seems also to be a suitable source for nanocellulose production.
Keywords: Acid hydrolysis; Imperata brasiliensis fibers; Nanocellulose